Prevalence of Premenstrual Syndrome in women of reproductive age (Research, Society and Development, 2021)
Aim: To verify the prevalence of PMS in women of reproductive age in the city of Parnaíba-PI, as well as to trace the clinical and sociodemographic profile of women with premenstrual syndrome. Method: This was a cross-sectional study with a quantitative approach that included a population of 705 participants of reproductive age. Sample data were collected through physical and online questionnaires with aim questions. Diagnosis was made using the SPM and TDPM scales, based on the ACOG and DSM-V, respectively. Results: The study showed a prevalence of 99.6% (CI99%: 0.001 - 0.014) for women with PMS, with a greater portion of this percentage classified as severe PMS, besides having physical and emotional disorders resulting from PMS. Conclusion: According to the study, it is recommended to carry out longitudinal studies in order to map and analyze the real factors that influence the emergence and persistence of PMS symptoms, as well as preventive measures for such consequences.